Lessons from Hepatocyte-Specific Cyp51 Knockout Mice: Impaired Cholesterol Synthesis Leads to Oval Cell-Driven Liver Injury - Lorbek, Gregor (Sci Rep, 2015)
We demonstrate unequivocally that defective cholesterol synthesis is an independent determinant of liver inflammation and fibrosis. We prepared a mouse hepatocyte-specific knockout (LKO) of lanosterol 14α-demethylase (CYP51) from the part of cholesterol synthesis that is already committed to cholesterol. LKO mice developed hepatomegaly with oval cell proliferation, fibrosis and inflammation, but without steatosis. The key trigger was reduced cholesterol esters that provoked cell cycle arrest, senescence-associated secretory phenotype and ultimately the oval cell response, while elevated CYP51 substrates promoted the integrated stress response. In spite of the oval cell-driven fibrosis being histologically similar in both sexes, data indicates a female-biased down-regulation of primary metabolism pathways and a stronger immune response in males. Liver injury was ameliorated by dietary fats predominantly in females, whereas dietary cholesterol rectified fibrosis in both sexes. Our data place defective cholesterol synthesis as a focus of sex-dependent liver pathologies.